PENGARUH SELEBRITIS, GAMBARAN MEREK DAN KUALITAS PRODUK TERHADAP MINAT BELI PEMBALUT WANITA MEREK LAURIER - Yunita Rosiana; Sugeng Purwanto (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The diversity of brands of sanitary napkins in Indonesia makes competition in similar industries tighter, of course, making consumers even more confused about buying a product that can interest them. One of the marketing strategies that companies can implement to attract consumers' buying interest is cooperating with a well-known celebrity. This study analyzes the Laurier product, a well-known brand, by cooperating with Vanesha Prescilla as a celebrity endorser. Laurier brand sanitary napkins belong to the category product Top Brand Index category but has experienced a significant decline yearly. This study aims to analyze the effect of celebrity endorsers, brand image, and product quality on the purchase intention of Laurier brand sanitary napkin products in Surabaya. The study used quantitative methods by distributing questionnaires. The sampling technique in this study applies accidental sampling with 105 respondents. The results of this study explain that celebrity endorsers, brand image, and product quality have a positive and significant influence on purchase intention